Evaluasi Penerapan Reward dan Punishment Bagi Nasabah Kredit Pada LPD Kesiman - Anindyanari, Ni Luh Putu Ayu; Suryathi, Wayan; Sukarta, I Wayan (Badung Bali: Politeknik Negeri Bali, 2023)
The growing LPD Kesiman faces various problems, especially the risk of non-performing loans. Efforts made to improve the smoothness of credit payments are by providing rewards and punishments for credit customers. This research was conducted to determine the application of reward and punishment for credit customers and the implications for LPD Kesiman. This research is a descriptive research with a qualitative approach, collecting data by observation, interviews, and documentation. The informants in this study were LPD Kesiman credit employees. The results showed that the implementation of reward and punishment for credit customers at the LPD Kesiman had gone well, rewards were given in the form of ease in managing credit, priority was given to credit, service and faster credit disbursement. Provision of punishment in the form of warning letters up to three times, summons to the LPD Kesiman office regarding bad credit constraints, as well as withdrawing credit collateral to be sold/auctioned to cover the amount of bad customer debt. The application of reward and punishment provides two types of implications for the Kesiman LPD, namely: the impact on credit development and the impact on the level of discipline of customers/debtors at the LPD Kesiman.